Auxiliary Subunits Regulate the Dendritic Turnover of AMPA Receptors in Mouse Hippocampal Neurons - Harb, Ali; Vogel, Nils; Shaib, Ali; Becherer, Ute; Bruns, Dieter; Mohrmann, Ralf (Frontiers in Molecular Neuroscience, 2021)
Different families of auxiliary subunits regulate the function and trafficking of native α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors in the central nervous system. While a facilitatory role of auxiliary subunits in ER export and forward trafficking of newly synthesized AMPA receptors is firmly established, it is unclear whether auxiliary subunits also control endosomal receptor turnover in dendrites. Here, we manipulated the composition of AMPA receptor complexes in cultured hippocampal neurons by overexpression of two auxiliary subunits, transmembrane AMPAR regulatory protein (TARP) gamma-8 or cysteine knot AMPAR-modulating protein (CKAMP) 44a, and monitored dendritic receptor cycling in live-cell imaging experiments. Receptor surface delivery was assayed using a modified AMPA receptor subunit carrying the pH-dependent fluorophore superecliptic pHluorin (SEP-GRIA1), which regains its fluorescence during receptor exocytosis, when transiting from the acidic lumen of transport organelles to the neutral extracellular medium. Strikingly, we observed a dramatic reduction in the spontaneous fusion rate of AMPA receptor-containing organelles in neurons overexpressing either type of auxiliary subunit. An analysis of intracellular receptor distribution also revealed a decreased receptor pool in dendritic recycling endosomes, suggesting that incorporation of TARPgamma-8 or CKAMP44a in receptor complexes generally diminishes cycling through the endosomal compartment. To directly analyse dendritic receptor turnover, we also generated a new reporter by N-terminal fusion of a self-labelling HaloTag to an AMPA receptor subunit (HaloTag-GRIA1), which allows for selective, irreversible staining of surface receptors. Pulse chase-experiments with HaloTag-GRIA1 indeed demonstrated that overexpression of TARPgamma-8 or CKAMP44a reduces the constitutive internalization rate of surface receptors at extrasynaptic but not synaptic sites. Thus, our data point to a yet unrecognized regulatory function of TARPgamma-8 and CKAMP44a, by which these structurally unrelated auxiliary subunits delay local recycling and increase surface lifetime of extrasynaptic AMPA receptors.